Contactless, probeless and non-titrimetric determination of acid–base reactions using broadband acoustic resonance dissolution spectroscopy (BARDS). Issue 4 (25th January 2018) - Ahmed, M. Rizwan; McSweeney, Sean; Krüse, Jacob; Vos, Bastiaan; Fitzpatrick, Dara
Abstract : Carbon dioxide production due to an acid–base reaction. Abstract : pH determination is a routine measurement in scientific laboratories worldwide. Most major advances in pH measurement were made in the 19th and early 20th century. pH measurements are critical for the determination of acid base reactions. This study demonstrates how an acid–base reaction can be monitored without the use of a pH probe, indicator and titres of reagent. The stoichiometric reaction between carbonate and HCl acid yields specific quantities of CO2, which causes reproducible changes to the compressibility of the solvent. This in turn slows down the speed of sound in solution which is induced by a magnetic follower gently tapping the inner wall of the vessel. As a consequence the frequencies of the acoustic resonances in the vessel are reduced. This approach is called Broadband Acoustic Resonance Dissolution Spectroscopy (BARDS) which harnesses this phenomenon for many applications. The acid-carbonate experiments have also been validated using H2 SO4 acid and using both potassium and sodium counterions for the carbonate. This method can be used to interrogate strong acid–base reactions in a rapid and non-invasive manner using carbonate as the base. The data demonstrate the first example of a reactant also acting as an indicator. The applicability of the method to weak acids has yet to be determined. A novel conclusion from the study is that a person with a well-trained ear is capable of determining the concentration and pH of a strong acid just by listening. This brings pH measurement into the realm of human perception.